PENGARUH PENYALURAN ALOKASI DANA DESA TERHADAP KESEJAHTERAAN MASYARAKAT DESA BALOMBONG KECAMATAN PELING TENGAH KABUPATEN BANGGAI KEPULAUAN - Samsidar, Samsidar; Yadasang, Rosfianti M. (Yayasan Education and Social Center, 2023)
The aim of this research is to find out whether the Village Fund Allocation has a positive and significant effect on the welfare of the people of Balombong Village, Peling Tengah District, Banggai Islands Regency. The sample in this research is the community of Balombong Village, Peling District, Banggai Islands Regency using purpose sampling technique with a total of 102 people. . Data collection methods use interviews and questionnaires. Data were analyzed descriptively quantitatively using frequency tables and simple linear regression. Results of data processing carried out using the SPSS version 25.0 program. From the results of the t test, it was found that the Village Fund Allocation variable (X) had a partial influence on the Welfare of the Village Community (Y) in Balombong Village, Peling District, Banggai Islands Regency. From the results of the coefficient test or t test, it was found that the t-count was 69.038 and the t-table was 1.663. This comparison means that it can be seen that the t-count = 69.038 > t-table = 1.663, which means it has a positive and significant effect on community welfare (Y) in Community of Balombong Village, Peling Tengah District, Banggai Islands Regency